2019
DOI: 10.3164/jcbn.19-3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the colonic mucosa associated microbiota (MAM) using brushing samples during colonic endoscopic procedures

Abstract: The mucosa associated microbiota is an important component in human microbiota. The aim was to investigate mucosa associated microbiota using brush samples during endoscopic procedures and compare with fecal microbiota. Seven patients who were planning to undergo a routine colonoscopy were recruited. Mucosal brushing samples were taken from 3 sites (terminal ileum, ascending and sigmoid colon), and a fecal sample was taken on the morning of colonoscopy. The samples were immediately placed in microcentrifuge tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…In the MAM, Bacteroidetes and Proteobacteria are more represented, while Firmicutes and Actinobacteria are more abundant in the LM [30] . Although the implications related to the different compositions of the MAM and the LM are still poorly understood, the MAM is more permanent and less susceptible to external factors, such as diet or stress [31] , and each bacterium found in the LM is found in the MAM, while some bacteria are exclusively present in the MAM. These differences are attributed to different antibacterial or mucosal factors, different oxygen tensions between the lumen and the mucosa and different access to nutrients [30] .…”
Section: Methodsmentioning
confidence: 99%
“…In the MAM, Bacteroidetes and Proteobacteria are more represented, while Firmicutes and Actinobacteria are more abundant in the LM [30] . Although the implications related to the different compositions of the MAM and the LM are still poorly understood, the MAM is more permanent and less susceptible to external factors, such as diet or stress [31] , and each bacterium found in the LM is found in the MAM, while some bacteria are exclusively present in the MAM. These differences are attributed to different antibacterial or mucosal factors, different oxygen tensions between the lumen and the mucosa and different access to nutrients [30] .…”
Section: Methodsmentioning
confidence: 99%
“…DNA was extracted as previously reported [7]. Preparation of library of amplicons encoding 16S rRNA gene and sequencing were conducted as described previously [17].…”
Section: Methodsmentioning
confidence: 99%
“…Thus, evaluating MAM in precise and accurate manners is recognized as a clinically important trial to characterize and understand the host-microbe interactions and their roles in the health promotion and disease prevention. We previously reported the difference in the bacterial community profile between brushing samples during endoscopic procedures and fecal samples [7]. Most previous studies investigating on the gut microbiota of IBS used fecal samples [8], and only a few studies investigated the MAM using biopsy samples [9-16].…”
Section: Introductionmentioning
confidence: 99%
“…In the annual meeting 2020, Matsumoto et al [22] indicated that the difference in the MAM between IBS-D and IBS-C using brushing samples taken from the ileum end and sigmoid of IBS patients and controls. The α-diversity and β-diversity indices were significantly different among the 3 groups (Fig.…”
Section: Gut Microbiome In Ibsmentioning
confidence: 99%
“… β-diversity PCoA UniFrac analysis weight ( a ), unweight ( b ): β-diversity analyses performed on all mucosal samples by UniFrac algorithms showed a separation among the 3 groups, and PCoA revealed microbial structural differences [22]. …”
Section: Gut Microbiome In Ibsmentioning
confidence: 99%